2011
DOI: 10.1111/j.2042-3306.2011.00515.x
|View full text |Cite
|
Sign up to set email alerts
|

Post operative infection, pyrexia and perioperative antimicrobial drug use in surgical colic patients

Abstract: SummaryReasons for performing study: Infections are common complications in post operative colic patients. It is the impression of some surgeons that pyrexia in the early post operative period is a sign of infection and appropriate timing of perioperative antimicrobials will decrease the incidence of post operative infection. Objective: To determine the association between 1) post operative pyrexia and development of infection and 2) perioperative antimicrobial drug use and infection rate in post operative col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
99
1
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(116 citation statements)
references
References 24 publications
11
99
1
5
Order By: Relevance
“…Long-term retrospective studies are challenging as from 14 to 44% of the horses are lost to follow-up [2, 7, 1416]. Missing data and small study population sizes may cause bias in statistical analysis and interpretation of results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term retrospective studies are challenging as from 14 to 44% of the horses are lost to follow-up [2, 7, 1416]. Missing data and small study population sizes may cause bias in statistical analysis and interpretation of results.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there are only two 24-h equine emergency hospitals in the southern part of Finland. This might cause delays in the initiation of the treatment, which worsens short- and long-term prognosis for colic patients [14, 16, 17, 19]. …”
Section: Discussionmentioning
confidence: 99%
“…This study revealed the majority of horses treated for surgical colic in our hospital received inaccurate antimicrobial prophylaxis, both in terms of dose received and when the drug was given. As clinical trials evaluating antimicrobial use in veterinary patients are limited, many institutions base antimicrobial use on consensus statements, recommendations for human patients, or common practice. The need for surgical prophylaxis has been demonstrated in veterinary surgery .…”
Section: Discussionmentioning
confidence: 99%
“…1 In small animal surgery, SSI range in frequency from 0.8-18.1%, depending on the procedure and contamination level and in equine surgery from 0 to 50%. 1,2 Adequate skin antisepsis is an important part of any invasive procedure. Two commonly used methods are a 5-minute preparation with mechanical scrubbing of the skin and a paint technique without mechanical scrubbing.…”
mentioning
confidence: 99%